Technological Changes and Skilled Manpower: The Automobile and Parts Manufacturing Industries - St-Laurent, Jacques (Relations industrielles / Industrial Relations, 1960)
The article reviews the book, "Technological Changes and Skilled Manpower: The Automobile and Parts Manufacturing Industries," issued by the Department of Labour, Canada, in co-operation with federal and provincial government agencies and other groups, September 1960 (54 pp.).